Longitudinal effects of gender minority stressors on substance use and related risk and protective factors among gender minority adolescents - Katz-Wise, Sabra L. (PLoS One, 2021)
PURPOSE: Gender minority (GM) adolescents, who have a different gender identity than their sex assigned at birth, may use substances as a coping strategy in response to GM-related stressors. This study examined longitudinal effects of gender minority stressors on substance use in GM adolescents, and related risk factors (internalized transphobia, depressive symptoms, anxious symptoms) and protective factors (resilience, gender-related pride, family functioning, social support, gender-related community connectedness). METHODS: Participants were 30 GM adolescents, ages 13–17 years, from the U.S. community-based longitudinal Trans Teen and Family Narratives Project. Participants completed an online survey every 6 months across 2 years (5 waves; data collected 2015–2019). RESULTS: Exposure to gender minority stressors was associated with higher odds of alcohol use. Across models, internalized transphobia (risk factor), resilience (protective factor), and gender-related pride (protective factor) were the most significant mediators of associations between gender minority stressors and substance use. Family functioning and social support (protective factors) significantly moderated the association between gender minority stressors and alcohol use, such that family functioning and social support were protective for alcohol use at lower levels of gender minority stress, but not at higher levels. CONCLUSION: Results suggest that GM adolescents engage in substance use as a coping strategy in response to gender minority stressors. A number of hypothesized risk and protective factors mediated or moderated these associations. Future interventions with GM adolescents should focus efforts on addressing internalized transphobia as a risk factor and strengthening resilience, gender-related pride, and family functioning as protective factors for substance use.